Persuasive argumentation mechanisms in the prose of Banu al-Ahmar - Narjis Ismail Radhi, Researcher; . Souad Badie Mutair, Assistant Professor Dr. (lark, 2026)
A study of Banu al-Ahmar’s prose reveals that it possessed a strong argumentative character. It was not merely a means by which the writer expressed a political or social position, but rather a rational persuasive tool based on diverse rhetorical and logical mechanisms. Writers employed argumentative ladders to arrange arguments according to an ascending logic, from weak to strong, thus enhancing the coherence of the discourse and clarifying the conclusion and bringing it closer to the recipient’s mind. Writers of this era also relied on a set of argumentative connectives, such as (but), (fa), and (waw), to create contrast, causality, or accumulation within the discourse. This enhanced textual cohesion and made arguments more impactful. In addition, the importance of argumentative factors, such as (condition, negation, restriction, and oath), emerged. These elements represented grammatical and semantic tools for restricting meaning, limiting it to a single direction, and removing illusions or doubts from the recipient’s mind. These tools were also reflected in the speeches and letters of the Banu al-Ahmar tribe, as a means of persuading the enemy, reassuring allies, or mobilizing fighters and urging them to jihad. The greatest value of this prose lies in its ability to blend logic and emotion, evidence and rhetoric, making persuasive discourse an effective tool for establishing religious, political, and social positions. Hence, it can be said that argumentative eloquence constituted the core of Banu al-Ahmar discourse and contributed significantly to consolidating a comprehensive rhetorical image that combined the beauty of language with the effectiveness of persuasion.